(untitled) (The Review of Diabetic Studies, 2023)
In the recent decades, oxidative stress has become focus of interest in most biomedical disciplines and many types of clinical research. Increasing evidence from research on several diseases show that oxidative stress is associated with the pathogenesis of diabetes, obesity, cancer, ageing, inflammation, neurodegenerative disorders, hypertension, apoptosis, cardiovascular diseases, and heart failure. Based on this research, the emerging concept is that oxidative stress is the “final common pathway”, through which risk factors of several diseases exert their deleterious effects. Oxidative stress causes a complex dysregulation of cell metabolism and cell-cell homeostasis. In this review, we discuss the role of oxidative stress in the pathogenesis of insulin resistance and beta-cell dysfunction. These are the two most relevant mechanisms in the pathophysiology of type 2 diabetes, and in the pathogenesis of diabetic vascular complications, the leading cause of death in diabetic patients.